Gold semicontinuous thin-film-coated mesoporous TiO2 for SERS substrates - Zalduendo, María Mercedes (2020)
In this work, the preparation and thermal evolution of sputtered semicontinuous gold thin films obtained over ordered mesoporous TiO2 films are presented. The controlled surface topography of the ordered mesoporous TiO2 substrate was used as template for obtaining plasmonic hotspots for Surface Enhanced Raman Spectroscopy (SERS) applications. Plasmonic thin film was obtained by Au sputtering when film thickness was under circa 10 nm. Above this value, the porosity effects from the substrate were lost and Raman signal enhancement with it. Moreover, heat treatment was explored in order to obtain gold nanoislands that can also provide very efficient Raman enhancement. Hence, a very straightforward synthesis procedure is presented for sensing application, even for large scale production.